Theoretical Study on the Consolidation of Multiple Composite Foundations with Vertical Drains-Impervious Piles considering Temperature Effect and Nonuniform Distribution of Initial Pore Pressure - Yuguo Zhang; Yamin Zhao; Chuang Wang; Wenbing Yang (Advances in Civil Engineering)
For the problem of consolidation of multiple composite foundations of vertical drain-impervious pile, considering the influence of temperature and nonuniform distribution of initial pore pressure, the consolidation control equations based on the assumption of equal strain are established, and the analytical solution method is adopted to give the analytical solution of consolidation of multiple composite foundations of the vertical drain-impervious pile with trapezoidal, rectangular, positive triangular, and inverted triangular distribution of initial pore pressure. The correctness and reasonableness of the solutions are verified by comparing the degenerate solutions of this paper with the existing solutions. The consolidation properties of the multifaceted composite foundation are analyzed according to the solution of this paper. The results show that the initial pore pressure is faster to consolidate in a trapezoidal distribution than in a rectangular distribution, fastest to consolidate in an inverted triangular distribution and slowest to consolidate in a positive triangular distribution. The rate of consolidation of a multiple composite foundation can be significantly accelerated by increasing the temperature, the replacement rate of impervious piles, and the compression modulus. The rate of consolidation of a multiple composite foundation can be significantly increased compared to a single pile type foundation; the size of the permeability coefficient of the vertical drain almost represents the size of the drainage capacity of the composite foundation. The rate of consolidation of a multiple composite foundation is faster as the permeability coefficient of the vertical drain increases.